Análise dos efeitos de RAP2A sobre a ativação do fator de transcrição NF-kappaB na via de sinalização celular dos receptores do tipo Toll (TLRs) - Brener Cunha Carvalho (2014)
Pathogen recognition, a key event for the initiation of innate immune response, is mediated by pattern-recognition receptors (PRRs) such as toll-like receptors (TLRs). Cell signaling triggered through TLRs leads to the activation of several transcription factors, which in turn participate in the regulation of genes related to inflammatory response. A critical transcription factor in this context is the NF-kB, which needs to be properly modulated by several mechanisms, as its dysregulation plays a key role in several diseases. Therefore, a better understanding of NF-кB modulation mechanisms may provide new therapeutic approaches for various diseases. RAP2A belongs to the Ras superfamily, a group of proteins involved in various cellular processes which have their activity regulated by molecules called GEFs and GAPs. Studies in our laboratory demonstrate that a GEF called RasGEF1B is encoded by a TLR-inducible gene and has a negative regulatory role on the NF-кB activation mediated by TLRs (Andrade et al, 2010; Rocha et al., 2014). In 2009, Yaman and colleagues (Yaman et al, 2009) described RAP2A as a RasGEF1B effector molecule. Thus, we hypothesized that RAP2A also plays an important regulatory role on the activity of NF-kB. Therefore, the main objective of this study was to evaluate the effect of RAP2A in the regulation of NF-kB activation in cell signaling pathways triggered by TLRs. First, we determined by RT-PCR and RT-qPCR the expression profile of RAP2A in response to stimulation with TLR agonists on murine macrophages and human monocytes. Interestingly, RAP2A levels are already elevated in unstimulated cells, but are dramatically reduced after TLR agonists stimulation. In transfection studies and reporter gene assays, we evaluated the effect of RAP2A on the NF-кB activation induced by various molecules such as TNF, TLRs agonists and downstream proteins of the TLRs signaling pathway. The results show that when overexpressed, RAP2A inhibits the activation of NFkappaB induced by these molecules, except by TLR3 agonist. Our data support the idea that RAP2A is an important molecule that contributes to the regulation of NF-kappaB activation in the immune response mediated by TLRs, and that a repression in its expression after exposure of cells to inflammatory agonists is a critical event to allow a successful activation of NF-kappaB.